Extracellular ATP protects against sepsis through macrophage P2X7 purinergic receptors by enhancing intracellular bacterial killing. Issue 9 (9th June 2015) - Csóka, Balázs; Németh, Zoltán H.; Törő, Gábor; Idzko, Marco; Zech, Andreas; Koscsó, Balázs; Spolarics, Zoltán; Antonioli, Luca; Cseri, Karolina; Erdélyi, Katalin; Pacher, Pál; Haskó, György
ABSTRACT: Extracellular ATP binds to and signals through P2X7 receptors (P2X7Rs) to modulate immune function in both inflammasome‐dependent and ‐independent manners. In this study, P2X7 ‐/‐ mice, the pharmacological agonists ATP‐magnesium salt (Mg‐ATP; 100 mg/kg, EC50 ≈ 1.32 mM) and benzoylbenzoyl‐ATP (Bz‐ATP; 10 mg/kg, EC50 ≈ 285 μM), and antagonist oxidized ATP (oxi‐ATP; 40 mg/kg, IC50 ≈ 100 μM) were used to show that P2X7R activation is crucial for the control of mortality, bacterial dissemination, and inflammation in cecal ligation and puncture‐induced polymicrobial sepsis in mice. Our results with P2X7 ‐/‐ bone marrow chimeric mice, adoptive transfer of peritoneal macrophages, and myeloid‐specific P2X7 ‐/‐ mice indicate that P2X7R signaling on macrophages is essential for the protective effect of P2X7Rs. P2X7R signaling protects through enhancing bacterial killing by macrophages, which is independent of the inflammasome. By using the connexin (Cx) channel inhibitor Gap27 (0.1 mg/kg, IC50 ≈ 0.25 μM) and pannexin channel inhibitor probenecid (10 mg/kg, IC50 ≈ 11.7 μM), we showed that ATP release through Cx is important for inhibiting inflammation and bacterial burden. In summary, targeting P2X7Rs provides a new opportunity for harnessing an endogenous protective immune mechanism in the treatment of sepsis.—Csóka, B., Németh, Z. H., Törő, G., Idzko, M., Zech, A., Koscsó, B., Spolarics, Z., Antonioli, L., Cseri, K., Erdélyi, K., Pacher, P., Haskó, G. Extracellular ATP protects against sepsis through macrophage P2X7 purinergic receptors by enhancing intracellular bacterial killing. FASEB J. 29, 3626‐3637 (2015). www.fasebj.org